Juridical Analysis Of The Implementation Of Compulsory Study At Night On Children In An Effort To Protect And Overcome Youth Delinquency (Research Study In Bintan District) - Winda Isnaeni; Ramon Nofrizal; Bachtiar Simatupang; Soerya Respationo; Erniyanti Erniyanti (FKIP, Universitas Palangka Raya, 2023)
Children and teenagers are the next generation of the nation and are family and state assets that must be safeguarded and protected in all aspects of their lives, including physical, psychological, intellectual, their rights, and their dignity. Protecting children is not only the responsibility of parents but also the responsibility of all of us. The purpose of this research is to determine the legal basis for the formation of policies for implementing compulsory school hours at night, the differences between the implementation of study hours at night and study hours during the day, goals and objectives, infrastructure, implementation, task force, duties and functions of the task force, and the sanctions and obstacles faced in implementing compulsory education at night. The specification method of this research is analytical descriptive, which describes finding legal facts systematically with the aim of making this research easier to understand and conclude. The results of the research show that there are efforts to protect and prevent juvenile delinquency from the Bintan Regency Government in the form of regional head policy, namely Regent's Regulation Number 66 of 2014 concerning Compulsory Night Study Hours for Children in Bintan Regency, which is in accordance with applicable regulations but is not yet effective because there are several obstacles in its implementation.